THE ROLE AND IMPORTANCE OF PROMOTION IN THE DEVELOPMENT OF GASTRONOMIC TOURISM OF THE REPUBLIC OF CROATIA - Batinic, Ivica (Journal of process management and new technologies, 2017)
Gastronomic travel is all the more popular all over the world, and gastronomic tourism has become a selective form of tourism aimed at creating a top tourist experience. Republic of Croatia is proud of its rich gastronomy in such a small area of outstanding cultural specificity and diversity, and with an interesting gastronomic offer tourists can be provided with completely different and new experiences. With a rich, attractive and autochthonous gastronomic offer that will have segments of new experiences and adventures as well as quality cooperation between state (development) institutions and tourist entities in tourist destinations, the Republic of Croatia can successfully develop and promote gastronomic tourism and become a recognizable world gastronomic destination on the demanding Tourism market.